2017
DOI: 10.1055/s-0042-122137
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas Transplantation Delays the Progression of Morphological, Morphometric and Ultrastructural Changes in Testes of Alloxan-Induced Diabetic Rats

Abstract: The aim of this study was to assess the effects of pancreas transplantation on the progression of testicular lesions in diabetic rats. Diabetic rats were subjected to pancreas transplantation and sacrificed after 6, 14, 26 and 50 weeks of follow-up, using non-diabetic and untreated diabetic rats as controls. Successful pancreas transplantation corrected all of the metabolic changes observed in diabetic rats, including low levels of testosterone. The testicular mass was decreased, and the relative weight of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The significant role of insulin has been shown by a study investigating the effects of pancreas transplantation in diabetic rats. Spadella et al showed that a successful pancreas transplantation in rats was able to impede the progression of the diabetic damage on the germ, Leydig and Sertoli cells (Tadeu Spadella et al, 2017). Exendin‐4 is an agonist of the glucagon‐like peptide 1 (GLP‐1) receptor, a peptide which promotes insulin secretion.…”
Section: Resultsmentioning
confidence: 99%
“…The significant role of insulin has been shown by a study investigating the effects of pancreas transplantation in diabetic rats. Spadella et al showed that a successful pancreas transplantation in rats was able to impede the progression of the diabetic damage on the germ, Leydig and Sertoli cells (Tadeu Spadella et al, 2017). Exendin‐4 is an agonist of the glucagon‐like peptide 1 (GLP‐1) receptor, a peptide which promotes insulin secretion.…”
Section: Resultsmentioning
confidence: 99%
“…It is estimated that roughly 5-12 % of women conceive after renal transplant, and that half of these pregnancies are unintended [24]. Recovery of male fertility after pancreas transplant is noted both in men and experimental animals [25]. Therefore, it is of crucial significance to provide enough information regarding safe contraception and planned pregnancies in transplant patients [1,26].…”
Section: Reviewmentioning
confidence: 99%